Negative electrode for sodium ion secondary battery, and sodium ion secondary battery
By using a double-layer structure of carbon material and sodium-containing alloy in the negative electrode of a sodium ion secondary battery, the problem of sodium ions being captured by the negative electrode during the first charge is solved, and the charge and discharge efficiency and cycle characteristics are improved.
Patent Information
- Application Number
- CN202380065295.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-20
- Filing Date
- 2023-12-18
- Publication Date
- 2025-04-25
AI Technical Summary
In a rocking chair-type sodium ion secondary battery, undesirable side reactions may occur during the first charge, resulting in the sodium ions being captured by the negative electrode, and the sodium ions being unable to return to the positive electrode during discharge, reducing the first charge and discharge efficiency.
Using a negative electrode structure including a first negative electrode active material containing a carbon material and a second negative electrode active material containing a sodium alloy, the unreturned sodium ions are supplied to the positive electrode layer through the second negative electrode layer, reducing the first irreversible capacity and improving the charge and discharge efficiency.
It effectively improves the first charge and discharge efficiency of sodium ion secondary batteries, reduces irreversible capacity, and optimizes the cycle characteristics.
Smart Images

Figure BDA0005306304920000281 
Figure BDA0005306304920000311 
Figure BDA0005306304920000331
Abstract
Description
Technical Field
[0001] The present invention relates to a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery using the negative electrode for a sodium ion secondary battery. Background Art
[0002] Lithium ion secondary batteries have established their position as high-capacity and lightweight power sources that are indispensable for mobile devices, electric vehicles, etc. However, in existing lithium ion secondary batteries, flammable organic electrolytes are mainly used as electrolytes, so there is a fear of dangers such as fire. As a method to solve this problem, people are promoting the development of all-solid-state batteries such as all-solid-state lithium ion batteries using solid electrolytes instead of organic electrolytes. However, there are problems with low ion conductivity, difficulty in low-temperature operation and high output in oxide-based solid electrolytes with lithium ion conductivity. Therefore, as an alternative, people are promoting the development of all-solid-state sodium ion secondary batteries (for example, patent document 1) using oxide-based solid electrolytes with sodium ion conductivity.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2010-15782. Summary of the invention
[0006] Problem that the invention aims to solve
[0007] As an all-solid-state sodium ion secondary battery, a "rocking chair" battery is known, in which a material containing sodium ions as carrier ions is used in the positive electrode active material, and a material containing no sodium ions is used in the negative electrode active material. As such a negative electrode active material, carbon materials such as graphite and hard carbon are known.
[0008] However, in the rocking chair type sodium ion secondary battery, undesirable side reactions sometimes occur during the first charge, resulting in sodium ions being captured by the negative electrode, and the sodium ions may not be able to return to the positive electrode during discharge. In this case, there is a problem that the first irreversible capacity is generated, and the ratio of the discharge capacity to the first charge capacity, that is, the first charge and discharge efficiency, is reduced.
[0009] An object of the present invention is to provide a negative electrode for a sodium ion secondary battery that can improve the initial charge and discharge efficiency of a secondary battery, and a sodium ion secondary battery using the negative electrode for a sodium ion secondary battery.
[0010] Technical means of solving problems
[0011] Various aspects of a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery that solve the above-mentioned problems will be described.
[0012] The negative electrode for a sodium ion secondary battery according to the first aspect of the present invention is characterized by comprising: a first negative electrode active material including a carbon material; and a second negative electrode active material including a sodium-containing alloy.
[0013] The negative electrode for a sodium ion secondary battery of the second embodiment is preferably, in the first embodiment, comprising: a first negative electrode layer containing the first negative electrode active material; and a second negative electrode layer containing the second negative electrode active material.
[0014] The negative electrode for a sodium ion secondary battery of the third embodiment is preferably such that, in the second embodiment, the second negative electrode layer also serves as a current collector.
[0015] The negative electrode for a sodium ion secondary battery of aspect 4 is preferably that, in any one of aspects 1 to 3, the sodium-containing alloy is an alloy containing Na and Sn.
[0016] The negative electrode for a sodium ion secondary battery of embodiment 5 is preferably that, in embodiment 4, the sodium-containing alloy is Na X Sn(0.16≤x≤3.75).
[0017] The negative electrode for a sodium ion secondary battery of aspect 6 is preferably such that, in any one of aspects 2 to 5, the thickness of the second negative electrode layer is 0.3 μm or more and 10 μm or less.
[0018] The negative electrode for a sodium ion secondary battery of aspect 7 is preferably that, in any one of aspects 1 to 6, the carbon material is hard carbon.
[0019] The negative electrode for a sodium ion secondary battery of aspect 8 is preferably, in any one of aspects 1 to 7, the negative electrode for a sodium ion secondary battery further contains a solid electrolyte.
[0020] The negative electrode for a sodium ion secondary battery of embodiment 9 is preferably such that, in embodiment 8, the solid electrolyte contains at least one selected from the group consisting of β″-alumina, β-alumina, and sodium superion conductor (NASICON) crystals.
[0021] The sodium ion secondary battery according to the tenth aspect of the present invention is characterized by comprising the negative electrode for a sodium ion secondary battery according to any one of the first to ninth aspects.
[0022] The sodium ion secondary battery of aspect 11 may be such that, in aspect 10, the negative electrode for the sodium ion secondary battery further includes a solid electrolyte layer, and the negative electrode for the sodium ion secondary battery is provided on one main surface of the solid electrolyte layer.
[0023] The sodium ion secondary battery of mode 12 may be, in mode 10 or mode 11, the negative electrode for the sodium ion secondary battery comprises: a first negative electrode layer, which is arranged on one side of the solid electrolyte layer and contains the first negative electrode active material; and a second negative electrode layer, which is arranged on the main surface of the first negative electrode layer on the opposite side to the solid electrolyte layer and contains the second negative electrode active material.
[0024] Effects of the Invention
[0025] According to the present invention, it is possible to provide a negative electrode for a sodium ion secondary battery that can improve the initial charge and discharge efficiency of a secondary battery, and a sodium ion secondary battery using the negative electrode for a sodium ion secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to a first embodiment of the present invention.
[0027] Figure 2 It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to a second embodiment of the present invention.
[0028] Figure 3 It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to a third embodiment of the present invention.
[0029] Figure 4 It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to a fourth embodiment of the present invention.
[0030] Figure 5 It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to a fifth embodiment of the present invention.
[0031] Figure 6 It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to a sixth embodiment of the present invention.
[0032] Figure 7 It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to a seventh embodiment of the present invention.
[0033] Figure 8 It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to an eighth embodiment of the present invention.
[0034] Fig. 9 It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to a ninth embodiment of the present invention. DETAILED DESCRIPTION
[0035] Hereinafter, preferred embodiments will be described. However, the following embodiments are merely examples, and the present invention is not limited to the following embodiments. In addition, in each of the drawings, components having substantially the same function are sometimes indicated by the same reference numerals.
[0036] [First embodiment]
[0037] Figure 1 It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to a first embodiment of the present invention.
[0038] like Figure 1 As shown, the sodium ion secondary battery 10 includes a solid electrolyte layer 2 , a positive electrode layer 3 , and a negative electrode layer 1 .
[0039] The solid electrolyte layer 2 has a first main surface 2a and a second main surface 2b facing each other. A positive electrode layer 3 is provided on the first main surface 2a of the solid electrolyte layer 2. In addition, a negative electrode layer 1 is provided on the second main surface 2b of the solid electrolyte layer 2. The negative electrode layer 1 is a first embodiment of the negative electrode for a sodium ion secondary battery of the present invention.
[0040] The negative electrode layer 1 includes a first negative electrode layer 4 and a second negative electrode layer 5. The first negative electrode layer 4 is provided on the second main surface 2b of the solid electrolyte layer 2. The first negative electrode layer 4 contains a first negative electrode active material containing a carbon material. In addition, the second negative electrode layer 5 is provided on the main surface of the first negative electrode layer 4 on the side opposite to the solid electrolyte layer 2. The second negative electrode layer 5 contains a second negative electrode active material containing a sodium alloy.
[0041] In the present embodiment, since the negative electrode layer 1 as the negative electrode for the sodium ion secondary battery has the above-mentioned structure, the initial charge and discharge efficiency of the sodium ion secondary battery 10 can be improved.
[0042] In the past, in a rocking-chair type sodium ion secondary battery, during the first charge, sodium ions as carrier ions moved from the positive electrode layer side to the negative electrode layer side, generating a reaction in which the negative electrode active material absorbed the sodium ions. However, during the first charge, undesirable side reactions sometimes occur, resulting in sodium ions being captured by the negative electrode layer, and the sodium ions may not be able to return to the positive electrode layer during discharge. For example, in the case where the negative electrode active material is composed of a carbon material such as hard carbon, there is a problem that sodium ions are captured by functional groups remaining in the carbon material during charge, and the sodium ions do not return to the positive electrode layer during discharge. In this case, there is a problem that the first irreversible capacity is generated in the sodium ion secondary battery, and the ratio of the discharge capacity to the first charge capacity, that is, the first charge and discharge efficiency, is reduced.
[0043] In contrast, in the present embodiment, the negative electrode layer 1 contains not only the first negative electrode active material containing the carbon material, but also the second negative electrode active material containing the sodium alloy. Therefore, when the sodium ion secondary battery 10 is charged and discharged for the first time, even if the sodium ions are captured by the first negative electrode layer 4 containing the carbon material, the sodium ions that have not returned to the positive electrode layer 3 can be supplied from the second negative electrode layer 5 containing the sodium alloy to the positive electrode layer 3. Thus, the first irreversible capacity of the sodium ion secondary battery 10 can be reduced, and the first charge and discharge efficiency can be improved.
[0044] In addition, in the present embodiment, since the negative electrode layer 1 as the negative electrode for the sodium ion secondary battery has the above-mentioned structure, the cycle characteristics of the sodium ion secondary battery 10 can be improved.
[0045] In the past, in sodium ion secondary batteries, when the negative electrode active material is composed of a carbon material such as hard carbon, if overcharge occurs during charging, sodium ions may be precipitated in the form of dendrites due to voltage drop. In this case, there is a problem that due to repeated charge and discharge in the sodium ion secondary battery, the dendrites crack and become fine powder, resulting in deterioration of the cycle characteristics.
[0046] In contrast, in the present embodiment, even when the cycle characteristics of the sodium ion secondary battery 10 deteriorate due to repeated charge and discharge, sodium ions can be supplied from the second negative electrode layer 5 to the positive electrode layer 3. As a result, the capacity of the sodium ion secondary battery 10 after repeated charge and discharge can be increased. Therefore, the sodium ion secondary battery 10 of the present embodiment also has excellent charge and discharge cycle characteristics.
[0047] In the sodium ion secondary battery 10 , the second negative electrode layer 5 disposed outside the negative electrode layer 1 contains a sodium-containing alloy, so the second negative electrode layer 5 also serves as a current collector layer. Therefore, the number of components in the sodium ion secondary battery 10 can be reduced.
[0048] However, the sodium ion secondary battery 10 may also have other collector layers. Other collector layers may be provided on the main surface of the positive electrode layer 3 on the side opposite to the solid electrolyte layer 2, or may be provided on the main surface of the negative electrode layer 1 on the side opposite to the solid electrolyte layer 2. Other collector layers may also be provided on the main surfaces of both the positive electrode layer 3 and the negative electrode layer 1 on the side opposite to the solid electrolyte layer 2.
[0049] In the present invention, it is preferred that the structure A include a first negative electrode layer 4 containing a carbon material as a negative electrode active material and a second negative electrode layer 5 containing a sodium alloy as a negative electrode active material are sequentially stacked on a solid electrolyte layer 2, as in the sodium ion secondary battery 10 .
[0050] By including structure A, sodium ions are supplied from the sodium-containing alloy of the second negative electrode layer 5 to the carbon material as the negative electrode active material of the first negative electrode layer 4, so that the first irreversible capacity (pre-doping) can be reduced, and the second negative electrode layer 5 containing the sodium alloy acts as a current collector, so the electronic conductivity of the negative electrode layer 1 is improved. As a result, the output characteristics of the sodium ion secondary battery 10 are further improved.
[0051] By disposing the second negative electrode layer 5 containing a sodium-containing alloy whose volume change due to sodium ion absorption and release is large as the outermost layer of the free surface as in structure A, the volume change of the sodium-containing alloy can be allowed. As a result, the cycle characteristics of the sodium ion secondary battery 10 are further improved.
[0052] In addition, the sodium ions that move from the positive electrode layer 3 through the solid electrolyte layer 2 during charging are received by the first negative electrode layer 4 containing carbon material. However, even if the battery falls into an overcharged state and the sodium ions that cannot be received are precipitated as metallic sodium, as long as there is a second negative electrode layer 5 containing a sodium alloy in the outermost layer as in Structure A, the sodium ions will be absorbed by the second negative electrode layer 5 instead of crystallizing in a dendrite (needle-shaped) manner, which can further reliably prevent deterioration and short circuits inside the battery.
[0053] Even in the case where the capacity of both the first negative electrode layer 4 and the second negative electrode layer 5 that can receive sodium ions decreases due to long-term cycling (in the case of capacity degradation), as long as there is a second negative electrode layer 5 containing a sodium-containing alloy with high wettability to metallic sodium in the outermost layer as in Structure A, metallic sodium can be dissolved and precipitated reversibly on the second negative electrode layer 5. As a result, sodium ions that can participate in charging and discharging can be replenished, thereby further suppressing the degradation of the cycle characteristics of the sodium ion secondary battery 10.
[0054] On the other hand, for structure B in which a sodium alloy negative electrode layer containing a sodium alloy as a negative electrode active material and a carbon material negative electrode layer containing a carbon material as a negative electrode active material are sequentially stacked on a solid electrolyte layer, when this structure B is included, sodium ions can be supplied from the sodium alloy to the carbon material as the negative electrode active material to reduce the initial irreversible capacity (pre-doping), but at this time the sodium alloy negative electrode layer shrinks in volume, so the ion conduction path is cut off at the interface between the layers, resulting in the possibility of deterioration of the cycle characteristics of the sodium ion secondary battery.
[0055] In addition, when the outermost layer is a carbon material negative electrode layer as in structure B, the electron conductivity is lower than that of the sodium alloy negative electrode layer, so the output characteristics of the sodium ion secondary battery may be reduced.
[0056] In addition, sodium-containing alloys have strong reducing power and are easily oxidized by air, moisture, and some organic solvents, so they need to be processed in an inert atmosphere. Therefore, it is necessary to form a solid electrolyte layer and a carbon material negative electrode layer in an inert atmosphere, which increases the manufacturing cost.
[0057] In particular, in structure B, when a carbon material negative electrode layer and a solid electrolyte layer are formed on the sodium alloy negative electrode layer by heat treatment, the sodium alloy will be deactivated due to oxidation or cause side reactions, and thus the effect of reducing the first irreversible capacity of the sodium ion secondary battery is easily reduced (the effect is easily reduced in either the case where a sodium alloy layer is formed on the solid electrolyte layer and then a carbon material negative electrode layer is formed by sintering, or in either the case where a sodium alloy layer is formed on the carbon material negative electrode layer and then a solid electrolyte layer is formed by sintering).
[0058] In addition, in the case of structure A in which a first negative electrode layer 4 containing a carbon material as a negative electrode active material and a second negative electrode layer 5 containing a sodium alloy as a negative electrode active material are sequentially stacked on a solid electrolyte layer 2, during and just after the formation of the second negative electrode layer 5 containing the sodium alloy in a vacuum process, sodium ions move toward the first negative electrode layer 4, reducing ability, and therefore the layer is not easily affected by oxidation.
[0059] Hereinafter, the details of each layer in the sodium ion secondary battery of the present invention will be described.
[0060] (Negative electrode layer)
[0061] The negative electrode layer 1 includes a first negative electrode layer 4 and a second negative electrode layer 5. The first negative electrode layer 4 includes a first negative electrode active material 6 and a solid electrolyte 7.
[0062] First negative electrode layer:
[0063] The first negative electrode layer 4 contains a first negative electrode active material 6. The first negative electrode active material 6 contains a carbon material. As the carbon material, hard carbon, soft carbon, graphite, etc. can be used. Among them, the carbon material is preferably hard carbon. In addition, the first negative electrode active material 6 can be composed only of carbon material, or it can contain carbon material and other components. As other components, Sn, Bi, Sb, Pb, Si, alloys containing them, etc. can be mentioned. Of course, the content of other components is preferably less than 10% by mass of the entire first negative electrode active material 6.
[0064] The first negative electrode layer 4 may further contain a conductive additive. The ratio of each material in the first negative electrode layer 4 may be, for example, 50% to 95% of the first negative electrode active material 6, 5% to 50% of the solid electrolyte 7, and 0% to 20% of the conductive additive in terms of mass %.
[0065] The content of the first negative electrode active material 6 in the first negative electrode layer 4 is preferably 50% or more, more preferably 60% or more, further preferably 70% or more, preferably 95% or less, more preferably 90% or less, further preferably 85% or less in terms of mass%. When the content of the first negative electrode active material 6 in the first negative electrode layer 4 is within the above range, the battery characteristics such as the charge and discharge capacity of the sodium ion secondary battery 10 can be more effectively improved.
[0066] The content of the solid electrolyte 7 in the first negative electrode layer 4 is preferably 5% or more, more preferably 10% or more, further preferably 15% or more, preferably 50% or less, more preferably 30% or less, and further preferably 25% or less in terms of mass %. When the content of the solid electrolyte 7 in the first negative electrode layer 4 is within the above range, the ion conductivity can be further improved, and the battery characteristics of the sodium ion secondary battery 10 can be more effectively improved.
[0067] In addition, the content of the conductive auxiliary agent in the first negative electrode layer 4 is preferably 0% or more, more preferably 0.1% or more, further preferably 0.5% or more, preferably 20% or less, more preferably 10% or less, and further preferably 8% or less in terms of mass%. When the content of the conductive auxiliary agent in the first negative electrode layer 4 is within the above range, the electronic conductivity can be further improved, and the battery characteristics of the sodium ion secondary battery 10 can be more effectively improved.
[0068] As the solid electrolyte 7, for example, a sodium ion conductive oxide can be used. As the sodium ion conductive oxide, there can be mentioned a compound containing at least one selected from Al, Y, Zr, Si and P, Na and O. As a specific example of the sodium ion conductive oxide, there can be mentioned Beta alumina or sodium super ion conductor (NASICON) crystals having excellent sodium ion conductivity. Among them, the sodium ion conductive oxide is preferably at least one sodium ion conductive oxide selected from the group consisting of β″-alumina, β-alumina and sodium super ion conductor (NASICON) crystals. The sodium ion conductive oxide is more preferably β-alumina or β″-alumina. They have better sodium ion conductivity.
[0069] Beta alumina has two crystal forms: β-alumina (theoretical composition formula: Na2O·11Al2O3) and β″-alumina (theoretical composition formula: Na2O·5.3Al2O3). β″-alumina is a metastable substance, so it is usually used with Li2O or MgO added as a stabilizer. Compared with β-alumina, β″-alumina has a higher sodium ion conductivity, so it is preferred to use β″-alumina alone or a mixture of β″-alumina and β-alumina, and it is more preferred to use Li2O stabilized β″-alumina (Na 1.7 Li 0.3 Al10.7 O 17 ) or MgO stabilized β″-alumina ((Al 10.32 Mg 0.68 O 16 )(Na 1.68 O)).
[0070] As sodium superion conductor (NASICON) crystals, there are: Na3Zr2Si2PO 12 、Na 3.2 Zr 1.3 Si 2.2 P 0.8 O 10.5 、Na3Zr 1.6 Ti 0.4 Si2PO 12 、Na3Hf2Si2PO 12 、Na 3.4 Zr 0.9 Hf 1.4 Al 0.6 Si 1.2 P 1.8 O 12 、Na3Zr 1.7 Nb 0.24 Si2PO 12 、Na 3.6 Ti 0.2 Y 0.8 Si 2.8 O9、Na3Zr 1.88 Y 0.12 Si2PO 12 、Na 3.12 Zr 1.88 Y 0.12 Si2PO 12 、Na 3.05 Zr2Si 2.06 P 0.95 O 12 、Na 3.4 Zr2Si 2.4 P 0.6 O 12 、Na 3.4 Zr 1.9 Mg 0.1 Si 2.4 P 0.6 O 12 、Na 3.4 Zr 1.9 Zn 0.1 Si 2.4 P 0.6 O 12 、Na 3.4 Zr 1.9 Mg0.1 Si 2.2 P 0.8 O 12 、Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 、Na 3.6 Zr 0.13 Yb 1.67 Si 0.11 P 2.9 O 12 、Na5YSi4O 12 As a sodium superionic conductor (NASICON) crystal, Na 3.4 Zr2Si 2.4 P 0.6 O 12 、Na3Zr 1.7 Nb 0.24 Si2PO 12 Or Na 3.05 Zr2Si 2.06 P 0.95 O 12 Since it is excellent in sodium ion conductivity, it is preferable.
[0071] The average particle size of the powder of the solid electrolyte 7 is preferably 0.05 μm to 3 μm, more preferably 0.05 μm to less than 1.8 μm, further preferably 0.05 μm to 1.5 μm, particularly preferably 0.1 μm to 1.2 μm, and most preferably 0.1 μm to 0.7 μm.
[0072] In the present invention, the average particle size refers to D50 (average particle size based on volume), which is a value measured by a laser diffraction scattering method.
[0073] As the conductive additive, for example, conductive carbon can be used. As conductive carbon, for example, acetylene black, carbon black, Ketjen black, vapor-grown carbon fiber (VGCF), carbon nanotubes, etc. The conductive additive is preferably a carbon-based conductive additive composed of the above materials.
[0074] The thickness of the first negative electrode layer 4 is preferably 5 μm or more, more preferably 20 μm or more, and preferably 200 μm or less, more preferably 100 μm or less. In this case, the charge and discharge capacity of the sodium ion secondary battery 10 can be further increased.
[0075] In addition, the loading amount (supporting amount) of the first negative electrode active material 6 in the first negative electrode layer 4 is preferably 0.15 mg / cm 2 More preferably, 1 mg / cm2 Above, preferably 10 mg / cm 2 Below, more preferably 5 mg / cm 2 In this case, the charge and discharge capacity of the sodium ion secondary battery 10 can be further increased.
[0076] Second negative electrode layer:
[0077] The second negative electrode layer 5 contains a second negative electrode active material. The second negative electrode active material contains a sodium-containing alloy. In the present embodiment, the second negative electrode layer 5 is composed of a film of a sodium-containing alloy as the second negative electrode active material. In addition, the second negative electrode layer 5 may be composed only of a sodium-containing alloy, or may contain a sodium-containing alloy and other components. As other components, Al, Cu, SUS, etc. may be cited. Of course, the content of other components is preferably less than 5% by mass of the entire second negative electrode layer 5.
[0078] As the sodium-containing alloy, there is no particular limitation, and for example, an alloy containing Na and one or more selected from Sn, Sb, Si, Pb, Bi, Fe, Mo, Co, Zn, Ni, Mg, and Au can be cited. Among them, as the sodium-containing alloy, an alloy containing Na and Sn is preferably used. In this case, the melting point of the sodium-containing alloy can be further improved, and the battery characteristics such as the charge and discharge capacity of the sodium ion secondary battery 10 can be further improved. By further improving the melting point of the sodium-containing alloy, the heat resistance of the second negative electrode layer 5 can be further improved, and the safety of the sodium ion secondary battery 10 can be further improved.
[0079] In the case where the sodium-containing alloy is an alloy containing Na and Sn, the sodium-containing alloy is preferably Na X Sn(0.16≤x≤3.75).
[0080] Na X The x in Sn is preferably 0.2 or more, more preferably 0.3 or more, further preferably 0.4 or more, and preferably 3.5 or less, more preferably 2.5 or less, further preferably 1.2 or less. X When x in Sn is greater than the above lower limit, the initial irreversible capacity of the sodium ion secondary battery 10 can be further reduced, and the initial charge and discharge efficiency can be further improved. X When x in Sn is equal to or less than the above upper limit, the melting point of the sodium-containing alloy can be further increased.
[0081] In addition, the thickness of the second negative electrode layer 5 is preferably 0.3 μm or more, more preferably 1 μm or more, preferably 10 μm or less, and more preferably 8 μm or less. When the thickness of the second negative electrode layer 5 is above the above lower limit, the first irreversible capacity of the sodium ion secondary battery 10 can be further reduced, and the first charge and discharge efficiency can be further improved. In addition, when the thickness of the second negative electrode layer 5 is below the above upper limit, the volume change caused by the absorption and release of sodium ions in the second negative electrode active material can be further reduced, and the charge and discharge cycle characteristics of the sodium ion secondary battery 10 can be further improved.
[0082] In addition, the loading amount of the second negative electrode active material in the second negative electrode layer 5 is preferably 0.1 mg / cm 2 More preferably, 0.5 mg / cm 2 Above, preferably 3.6 mg / cm 2 Below, more preferably 1.5 mg / cm 2 Below. When the loading amount of the second negative electrode active material in the second negative electrode layer 5 is above the above lower limit, the first irreversible capacity of the sodium ion secondary battery 10 can be further reduced, and the first charge and discharge efficiency can be further improved. In addition, when the loading amount of the second negative electrode active material in the second negative electrode layer 5 is below the above upper limit, the volume change caused by the absorption and release of sodium ions in the second negative electrode active material can be further reduced, and the charge and discharge cycle characteristics of the sodium ion secondary battery 10 can be further improved.
[0083] The ratio of the loading amount of the second negative electrode active material in the second negative electrode layer 5 to the loading amount of the first negative electrode active material in the first negative electrode layer 4 (second negative electrode layer 5 / first negative electrode layer 4) is preferably 0.9 or more, more preferably 5 or more, further preferably 6 or more, preferably 25 or less, more preferably 15 or less, and further preferably 10 or less. When the above-mentioned loading amount ratio (second negative electrode layer 5 / first negative electrode layer 4) is above the above-mentioned lower limit, the first irreversible capacity of the sodium ion secondary battery 10 can be further reduced, and the first charge and discharge efficiency can be further improved. In addition, when the above-mentioned loading amount ratio (second negative electrode layer 5 / first negative electrode layer 4) is below the above-mentioned upper limit, the volume change caused by the absorption and release of sodium ions in the second negative electrode active material can be further reduced, and the charge and discharge cycle characteristics of the sodium ion secondary battery 10 can be further improved.
[0084] (Method for producing negative electrode layer)
[0085] Formation of the first negative electrode layer:
[0086] First, a solid electrolyte precursor is prepared. In this stage, a solid electrolyte precursor solution is preferably prepared. Specific examples of the solid electrolyte precursor and its solution are described later.
[0087] Next, the solid electrolyte precursor solution is dried. Thus, a solid electrolyte precursor is obtained. Next, the solid electrolyte precursor is crushed into a powder and mixed with a conductive aid as needed to form a mixed powder. Next, the solid electrolyte precursor powder or the mixed powder is mixed with a carbon material powder as a raw material of the first negative electrode active material 6 to obtain a negative electrode composite material powder. Next, in an organic solvent, the negative electrode composite material powder is mixed with a binder as needed. The organic solvent can use N-methyl-2-pyrrolidone, etc. Thus, a slurry is obtained.
[0088] The average particle size of the carbon material powder as the raw material of the first negative electrode active material 6 is not particularly limited, but is preferably 0.1 μm to 10 μm, more preferably 0.2 μm to 7 μm, further preferably 0.3 μm to 5 μm, and particularly preferably 0.5 μm to 1.5 μm.
[0089] Next, the slurry is applied to the second main surface 2b of the solid electrolyte layer 2 described later and dried. In this way, a lamination process of laminating the solid electrolyte layer 2 and the negative electrode material layer is performed. Next, the laminate of the solid electrolyte layer 2 and the slurry as the negative electrode material layer is fired. Thus, the first negative electrode layer 4 can be formed on the second main surface 2b of the solid electrolyte layer 2.
[0090] The drying temperature of the slurry is not particularly limited, and can be, for example, 30° C. to 350° C. The drying time of the slurry is not particularly limited, and can be, for example, 5 minutes to 600 minutes.
[0091] The firing temperature (maximum temperature) during the firing is preferably 600° C. or higher, more preferably 700° C. or higher, and preferably 1200° C. or lower, more preferably 1000° C. or lower. The holding time at the firing temperature can be, for example, 30 minutes to 3 hours.
[0092] In addition, the above-mentioned firing can be carried out in an inert atmosphere, for example. For example, the above-mentioned firing can be carried out in an atmosphere of N2, Ar, Ne or He, or can also be carried out in a vacuum. In addition, the firing can also be carried out in a reducing atmosphere containing H2. In the case of firing in an inert atmosphere or a reducing atmosphere, the initial charge and discharge efficiency can be further improved, so it is preferred. In addition, if the negative electrode material layer is not oxidized or oxidatively decomposed during firing, a small amount of oxygen may be contained in the atmosphere. The oxygen concentration can be, for example, greater than 0.1 ppm and less than 1000 ppm, but is not limited thereto.
[0093] Solid electrolyte precursor and its solution:
[0094] When the solid electrolyte is beta alumina, the solid electrolyte precursor can be obtained by mixing, for example, aluminum nitrate, sodium nitrate, lithium nitrate, etc. At this time, the ratio of each material is adjusted so as to achieve the target composition ratio of the solid electrolyte.
[0095] In the case of solid electrolytes such as sodium superion conductor (NASICON) type crystals or Na5XSi4O 12 In the case of a solid electrolyte precursor solution, a solution containing sodium element, transition metal element, and carbonate ion constituting a solid electrolyte can be cited as a solid electrolyte precursor solution (X is selected from at least one of the third group transition metal elements, preferably rare earth elements). In addition, in the solution, the sodium element exists in the state of sodium ions, and the transition metal element exists in the state of transition metal ions. The solid electrolyte precursor is composed of, for example, a gelled substance or a dried substance of the solid electrolyte precursor solution. Moreover, the solid electrolyte is composed of a sintered substance of the solid electrolyte precursor.
[0096] In addition, in the solid electrolyte precursor solution, for example, a solution containing nitrate ions may be used instead of carbonate ions, without particular limitation.
[0097] In addition, in the solid electrolyte precursor solution, the carbonate ion is preferably bidentately coordinated to the transition metal element. In this case, the transition metal element is likely to exist stably in the solution.
[0098] In addition, the solid electrolyte precursor solution preferably contains NR 4+ (In the formula, each R is a substituent independently selected from at least one of H, CH3, C2H5 and CH2CH2OH.) In this way, the transition metal element can easily exist stably in the solution.
[0099] The solid electrolyte precursor solution can be obtained by, for example, mixing water glass (sodium silicate), sodium tripolyphosphate, and an aqueous zirconium carbonate ammonia solution.
[0100] Adhesives:
[0101] The binder is a material used to integrate the raw materials (raw material powders) with each other. Examples of the binder include cellulose derivatives such as carboxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxypropyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxymethyl cellulose, or water-soluble polymers such as polyvinyl alcohol, thermosetting polyimide, phenolic resin, epoxy resin, urea resin, melamine resin, unsaturated polyester resin, polyurethane, and other thermosetting resins, polycarbonate resins such as polypropylene carbonate, acrylic resins such as polyvinylidene fluoride and polyacrylic acid, polyvinyl acetal, polyvinyl butyral, and the like.
[0102] Formation of the second negative electrode layer:
[0103] Next, a second negative electrode layer 5 is formed on the main surface of the first negative electrode layer 4 on the opposite side to the solid electrolyte layer 2. As a method for forming the second negative electrode layer 5, for example, a method for forming a sodium alloy film by a gas phase synthesis method can be cited. The gas phase synthesis method preferably uses a vacuum evaporation method. For example, a raw material for forming a sodium alloy film is placed in a tungsten wire basket, etc., and the surface of the first negative electrode layer 4 as the film forming surface is arranged directly above it in a manner opposite to the raw material. Next, the raw material for forming a sodium alloy film is heated in a vacuum to vaporize it. The vaporized sodium-containing alloy adheres to the surface of the first negative electrode layer 4, thereby forming a film. In addition, the second negative electrode layer 5 can also be formed by a physical vapor phase method such as a vacuum evaporation method and a sputtering method, a chemical vapor phase method such as a thermal CVD, MOCVD, and a plasma CVD, without particular limitation. By forming the second negative electrode layer 5 by a gas phase synthesis method, it can be firmly bonded to the first negative electrode layer 4, showing excellent battery performance. In particular, the output performance and cycle characteristics can be improved. In addition, the above-mentioned film forming technology uses a vacuum process, so the reaction between the sodium-containing alloy and the atmospheric components during film formation can be suppressed. This can particularly improve the initial charge and discharge efficiency, which is more preferable.
[0104] (Solid electrolyte layer)
[0105] The solid electrolyte constituting the solid electrolyte layer 2 is preferably formed of a sodium ion conductive oxide. As the sodium ion conductive oxide, the substances described in the section of the negative electrode layer can be used.
[0106] The solid electrolyte layer 2 can be manufactured by mixing raw material powders, shaping the mixed raw material powders, and then firing them. For example, it can be manufactured by slurrying the raw material powders to prepare a green sheet, and then firing the green sheet. Alternatively, it can be manufactured by a sol-gel method.
[0107] The thickness of the solid electrolyte layer 2 is preferably in the range of 5 μm to 1000 μm, more preferably in the range of 10 μm to 200 μm. If the thickness of the solid electrolyte layer 2 is too thin, the mechanical strength is reduced and it is easy to break, so it is easy to cause an internal short circuit. If the thickness of the solid electrolyte layer 2 is too thick, the sodium ion conduction distance accompanying charge and discharge becomes longer, so the internal resistance becomes higher, and the discharge capacity and operating voltage are easily reduced. In addition, the energy density per unit volume of the sodium ion secondary battery 10 is also easily reduced.
[0108] (Positive electrode layer)
[0109] The positive electrode active material contained in the positive electrode layer 3 is not particularly limited, but is preferably composed of a material having the general formula Na x M y P2Oz The positive electrode active material is composed of a crystallized glass of a crystal represented by (1≤x≤2.8, 0.95≤y≤1.6, 6.5≤z≤8, M is at least one selected from Fe, Ni, Co, Mn and Cr). Among them, it is more preferable to use a material containing the general formula Na x A positive electrode active material composed of a crystallized glass represented by MP2O7 (1≤x≤2, M is at least one selected from Fe, Ni, Co, Mn and Cr). As such a positive electrode active material crystal, for example, Na2FeP2O7, Na2CoP2O7, Na2NiP2O7, etc. can be used.
[0110] Wherein, crystallized glass refers to the precursor glass containing amorphous phase is heated (fired) to make crystals precipitate (crystallize) and obtain. Amorphous phase can be completely transformed into crystalline phase, or residual amorphous phase can be used. In addition, one crystal can be precipitated, or more than two crystals can be precipitated. For example, crystallized glass can be judged as crystallized glass according to the peak angle given by powder X-ray diffraction (XRD).
[0111] The positive electrode layer 3 may also contain a solid electrolyte and a conductive additive. The proportions of the materials in the positive electrode layer 3 may be, for example, 60% to 99.9% of the positive electrode active material, 0% to 30% of the solid electrolyte, and 0.1% to 10% of the conductive additive in terms of mass %.
[0112] In addition, as the solid electrolyte and the conductive auxiliary agent, for example, the substances described in the section of the negative electrode layer can be used.
[0113] The positive electrode layer 3 can be formed, for example, by forming an electrode material layer containing a positive electrode active material precursor and, as required, a solid electrolyte powder and a conductive aid on one main surface of the solid electrolyte layer 2, and firing the electrode material layer. The electrode material layer can be obtained, for example, by applying a slurry containing a positive electrode active material precursor and, as required, a solid electrolyte powder and a conductive aid and drying it. The slurry can contain a binder, a plasticizer or a solvent as required. In addition, the electrode material layer can also be a powder compact.
[0114] The drying temperature of the slurry is not particularly limited, and can be, for example, 30° C. to 150° C. The drying time of the slurry is not particularly limited, and can be, for example, 5 minutes to 600 minutes.
[0115] The firing atmosphere is preferably a reducing atmosphere. The firing temperature (maximum temperature) can be, for example, 400° C. to 600° C., and the holding time at the temperature can be, for example, 5 minutes to less than 3 hours.
[0116] Positive electrode active material precursor:
[0117] The positive electrode active material precursor (positive electrode active material precursor powder) is preferably composed of an amorphous oxide material that can generate active material crystals by firing. When the positive electrode active material precursor powder is composed of an amorphous oxide material, active material crystals can be generated during firing, and softened and flowed to form a dense positive electrode layer 3. In addition, when the positive electrode layer 3 contains a solid electrolyte, the positive electrode active material and the solid electrolyte can also be integrated. Alternatively, when the positive electrode layer 3 is in contact with the solid electrolyte layer 2, the two can be integrated. As a result, an ion conduction path can be formed better, so it is preferred. In addition, in the present invention, "amorphous oxide material" is not limited to completely amorphous oxide materials, but also includes materials containing a portion of crystals (for example, a crystallinity of less than 10%).
[0118] In the positive electrode active material precursor powder, it is preferred to contain 25% to 55% of Na2O, 10% to 30% of Fe2O3+Cr2O3+MnO+CoO+NiO and 25% to 55% of P2O5 in terms of mole % of the following oxides. The reasons for limiting the composition are described below. In addition, in the description of the content of each component below, "%" means "mole %" unless otherwise specified.
[0119] Na2O is the general formula Na x M y P2O z (M is at least one transition metal element selected from Cr, Fe, Mn, Co and Ni, 1≤x≤2.8, 0.95≤y≤1.6, 6.5≤z≤8) The main component of the active material crystal is shown. The content of Na2O is preferably 25% to 55%, and more preferably 30% to 50%. When the content of Na2O is within the above range, the charge and discharge capacity of the sodium ion secondary battery 10 can be further increased.
[0120] Fe2O3, Cr2O3, MnO, CoO and NiO are also of the general formula Na x M y P2O zThe main component of the active material crystals shown. The content of Fe2O3+Cr2O3+MnO+CoO+NiO is preferably 10% to 30%, and more preferably 15% to 25%. When the content of Fe2O3+Cr2O3+MnO+CoO+NiO is above the above lower limit, the charge and discharge capacity of the sodium ion secondary battery 10 can be further increased. On the other hand, when the content of Fe2O3+Cr2O3+MnO+CoO+NiO is below the above upper limit, it is possible to make it difficult for undesirable crystals such as Fe2O3, Cr2O3, MnO, CoO or NiO to precipitate. In addition, in order to further improve the cycle characteristics of the sodium ion secondary battery 10, it is preferred to actively contain Fe2O3. The content of Fe2O3 is preferably 1% to 30%, more preferably 5% to 30%, further preferably 10% to 30%, and particularly preferably 15% to 25%. The content of each component of Cr2O3, MnO, CoO and NiO is preferably 0% to 30%, more preferably 10% to 30%, and further preferably 15% to 25%. In addition, when at least two components selected from Fe2O3, Cr2O3, MnO, CoO and NiO are contained, the total amount is preferably 10% to 30%, and more preferably 15% to 25%.
[0121] P2O5 is also a general formula Na x M y P2O z The content of P2O5 is preferably 25% to 55%, and more preferably 30% to 50%. When the content of P2O5 is within the above range, the charge and discharge capacity of the sodium ion secondary battery 10 can be further increased.
[0122] In addition to the above-mentioned components, the positive electrode active material precursor powder may also contain V2O5, Nb2O5, MgO, Al2O3, TiO2, ZrO2 or Sc2O3. These components have the effect of improving electrical conductivity (electronic conductivity), and the rapid charge and discharge characteristics of the sodium ion secondary battery 10 are easily improved. The content of the above-mentioned components is preferably 0% to 25% in total, and more preferably 0.2% to 10%. When the content of the above-mentioned components is below the above-mentioned upper limit value, it is not easy to produce heterogeneous crystals that do not contribute to the battery characteristics, and the charge and discharge capacity of the sodium ion secondary battery 10 can be further increased.
[0123] In addition, the positive electrode active material precursor powder may contain SiO2, B2O3, GeO2, Ga2O3, Sb2O3 or Bi2O3 in addition to the above-mentioned components. By containing these components, the glass forming ability is further improved, and it is easy to obtain a more homogeneous positive electrode active material precursor powder. The content of the above-mentioned components is preferably 0% to 25% in total, and more preferably 0.2% to 10%. These components do not contribute to the battery characteristics, so if their content is too much, the charge and discharge capacity of the sodium ion secondary battery 10 tends to decrease.
[0124] The positive electrode active material precursor powder is preferably prepared by melting and molding a raw material batch. According to this preparation method, it is easy to obtain an amorphous positive electrode active material precursor powder with excellent homogeneity, so it is preferred. Specifically, the positive electrode active material precursor powder can be prepared as follows.
[0125] First, raw materials are prepared in a manner to obtain a raw material batch in a desired composition. Next, the obtained raw material batch is melted. The melting temperature can be appropriately adjusted in a manner that the raw material batch is homogeneously melted. For example, the melting temperature is preferably 800° C. or more, more preferably 900° C. or more. The upper limit of the melting temperature is not particularly limited, but if the melting temperature is too high, it will lead to energy loss, evaporation of sodium components, etc., and therefore it is preferably 1500° C. or less, more preferably 1400° C. or less.
[0126] The obtained molten material is then formed into a film by any method, for example, the molten material may be flowed between a pair of cooling rolls and formed into a film while being rapidly cooled, or the molten material may be flowed into a casting mold and formed into an ingot.
[0127] Next, the obtained compact is pulverized to obtain a positive electrode active material precursor powder. The average particle size of the positive electrode active material precursor powder is preferably 0.01 μm or more and less than 0.7 μm, more preferably 0.03 μm or more and 0.6 μm or less, further preferably 0.05 μm or more and 0.6 μm or less, and particularly preferably 0.1 μm or more and 0.5 μm or less.
[0128] Adhesives:
[0129] As the binder, the binder described in the section of the first negative electrode layer 4 can be used.
[0130] In addition, the thickness of the positive electrode layer 3 is preferably 10 μm or more, more preferably 30 μm or more, further preferably 50 μm or more, particularly preferably 70 μm or more, and most preferably 100 μm or more. In this case, the charge and discharge capacity of the sodium ion secondary battery 10 can be further improved. On the other hand, if the thickness of the positive electrode layer 3 is too thick, the impedance of electronic conduction becomes large, and the discharge capacity and operating voltage of the sodium ion secondary battery 10 may be reduced. In addition, the stress caused by shrinkage during firing becomes large, which may cause peeling, so the thickness of the positive electrode layer 3 is preferably 1000 μm or less.
[0131] In addition, the loading amount of the positive electrode active material in the positive electrode layer 3 is preferably 1 mg / cm 2 More preferably 3 mg / cm 2 More preferably, 5 mg / cm 2 Above, particularly preferably 7 mg / cm 2 Above, most preferably 10 mg / cm 2 In this case, the capacity of the sodium ion secondary battery 10 can be further increased. In addition, the upper limit of the amount of the positive electrode active material loaded in the positive electrode layer 3 is not particularly limited, and can be set to 30 mg / cm 2 .
[0132] (Other current collector layers)
[0133] As the material of other collector layers, there is no particular limitation, and metal materials such as aluminum, titanium, silver, copper, stainless steel or their alloys can be used respectively. The above metal materials can be used alone or in combination. Among them, their alloys refer to alloys containing at least one of the above metals. The thickness of other collector layers is not particularly limited, and can be 0.01 μm or more and 1000 μm or less.
[0134] As the formation method of other collector layers, there is no particular limitation, for example, physical vapor methods such as evaporation or sputtering, chemical vapor methods such as thermal CVD, MOCVD, and plasma CVD can be cited. As other formation methods of other collector layers, liquid phase film forming methods based on electroplating, sol-gel method, and spin coating can be cited. However, when other collector layers are formed on the positive electrode layer 3 and the negative electrode layer 1 by sputtering, respectively, it is preferred because of excellent adhesion.
[0135] [Second to fifth embodiments]
[0136] (Second Embodiment)
[0137] Figure 2 It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to a second embodiment of the present invention.
[0138] like Figure 2 As shown, in the negative electrode layer 21 (negative electrode for sodium ion secondary battery) of the sodium ion secondary battery 20, the first negative electrode layer 24 includes a first negative electrode active material 6 and a mixed phase 27. The first negative electrode active material 6 can use the material described in the first embodiment. The mixed phase 27 is composed of a mixture of hard carbon and a solid electrolyte.
[0139] The content of the first negative electrode active material 6 in the first negative electrode layer 24 is preferably 20% or more, more preferably 30% or more, further preferably 37% or more, preferably 85% or less, more preferably 70% or less, further preferably 60% or less in terms of mass %. When the content of the first negative electrode active material 6 in the first negative electrode layer 24 is within the above range, the battery characteristics such as the charge and discharge capacity of the sodium ion secondary battery 20 can be more effectively improved.
[0140] The content of the mixture phase 27 in the first negative electrode layer 24 is preferably 15% or more, more preferably 30% or more, further preferably 40% or more, preferably 90% or less, more preferably 70% or less, and further preferably 60% or less in terms of mass %. When the content of the mixture phase 27 in the first negative electrode layer 24 is within the above range, the ion conductivity and the electrical conductivity can be further improved, and the battery characteristics of the sodium ion secondary battery 20 can be more effectively improved.
[0141] The content of hard carbon contained in the mixed phase 27 is not particularly limited, but is preferably 60% by mass or more, more preferably 70% by mass or more, preferably 90% by mass or less, and more preferably 80% by mass or less. In this case, the conductivity of the first negative electrode layer 24 can be further improved, and the charge and discharge capacity of the sodium ion secondary battery 20 can be further improved.
[0142] The content of the solid electrolyte contained in the mixed phase 27 is not particularly limited, but is preferably 10 mass % or more, more preferably 20 mass % or more, and preferably 40 mass % or less, more preferably 30 mass % or less. In this case, the ion conductivity of the first negative electrode layer 24 can be further improved.
[0143] In addition, the first negative electrode layer 24 can be formed by, for example, the following method.
[0144] First, prepare a slurry containing a carbon material precursor and a solid electrolyte. When preparing the slurry, first, prepare a solid electrolyte precursor. In addition, at this stage, it is preferred to prepare a solid electrolyte precursor solution. Specific examples of solid electrolyte precursors and their solutions are described later. In addition, prepare a carbon material precursor (a precursor of a carbon material composed of hard carbon). The carbon material precursor can use appropriate sugars, biomass or polymers, etc.
[0145] When sugar is used as the carbon material precursor, for example, sucrose, cellulose, D-glucose, sucrose, etc. are mentioned. When biomass is used as the carbon material precursor, for example, corn stalks, sorghum stalks, pine cones, mangosteen, argan nut shells, rice husks, dandelions, cereal straw cores, ramie fibers, cotton, kelp, coconut endocarp, etc. are mentioned. When polymers are used as the carbon material precursor, for example, PAN (polyacrylonitrile), asphalt, PVC (polyvinyl chloride) nanofibers, polyaniline, sodium polyacrylate, tires (polymers for tires), phosphorus-doped PAN, etc. are mentioned.
[0146] Next, the solid electrolyte precursor solution and the carbon material precursor are mixed and then dried. Thus, a powder of a mixture of the solid electrolyte precursor and the carbon material precursor is obtained. Next, hard carbon powder as the first negative electrode active material 6 is added to the powder of the above mixture, and then mixed with a conductive additive and a binder in an organic solvent as needed. The organic solvent can be, for example, N-methyl-2-pyrrolidone. Thus, a slurry is obtained.
[0147] Thus, the second embodiment is the same as the first embodiment except that the carbon material precursor powder is added to the solid electrolyte precursor solution to form a mixed powder.
[0148] As in the second embodiment, the first negative electrode layer 24 may include a particulate first negative electrode active material 6 and a mixed phase 27 composed of a mixture of hard carbon and a solid electrolyte.
[0149] (Third Embodiment)
[0150] Figure 3 It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to a third embodiment of the present invention.
[0151] like Figure 3 As shown, in the negative electrode layer 31 of the sodium ion secondary battery 30 , the first negative electrode layer 34 is composed of a mixed phase 37 of a first negative electrode active material including a carbon material and a solid electrolyte.
[0152] As the first negative electrode active material, hard carbon formed using a carbon material precursor described later can be used.
[0153] The content of the first negative electrode active material in the first negative electrode layer 34 is preferably 20% or more, more preferably 50% or more, further preferably 70% or more, preferably 95% or less, more preferably 90% or less, further preferably 80% or less in terms of mass %. When the content of the first negative electrode active material in the first negative electrode layer 34 is within the above range, the battery characteristics such as the charge and discharge capacity of the sodium ion secondary battery 30 can be more effectively improved.
[0154] The content of the solid electrolyte in the first negative electrode layer 34 is preferably 5% or more, more preferably 10% or more, further preferably 20% or more, preferably 80% or less, more preferably 50% or less, and further preferably 30% or less in terms of mass %. When the content of the solid electrolyte in the first negative electrode layer 34 is within the above range, the ion conductivity can be further improved, and the battery characteristics of the sodium ion secondary battery 30 can be more effectively improved.
[0155] In addition, the first negative electrode layer 34 can be formed by, for example, the following method.
[0156] First, a slurry containing a carbon material precursor and a solid electrolyte is prepared. When preparing the slurry,
[0157] First, prepare a solid electrolyte precursor. In addition, at this stage, it is preferred to prepare a solid electrolyte precursor solution. Specific examples of solid electrolyte precursors and solutions thereof are described later. Furthermore, prepare a carbon material precursor (a precursor of a carbon material composed of hard carbon). The carbon material precursor can use appropriate sugars, biomass or polymers, etc.
[0158] When sugar is used as the carbon material precursor, for example, sucrose, cellulose, D-glucose, sucrose, etc. are mentioned. When biomass is used as the carbon material precursor, for example, corn stalks, sorghum stalks, pine cones, mangosteen, argan nut shells, rice husks, dandelions, cereal straw cores, ramie fibers, cotton, kelp, coconut endocarp, etc. are mentioned. When polymers are used as the carbon material precursor, for example, PAN (polyacrylonitrile), asphalt, PVC (polyvinyl chloride) nanofibers, polyaniline, sodium polyacrylate, tires (polymers for tires), phosphorus-doped PAN, etc. are mentioned.
[0159] Next, the solid electrolyte precursor solution and the carbon material precursor are mixed and then dried. Thus, a powder of a mixture of the solid electrolyte precursor and the carbon material precursor is obtained. Then, the powder of the above mixture is further mixed with a conductive auxiliary agent and a binder as needed in an organic solvent. For example, N-methyl-2-pyrrolidone can be used as the organic solvent. Thus, a slurry is obtained.
[0160] Thus, the third embodiment is the same as the second embodiment except that the hard carbon powder is not added to the slurry.
[0161] As in the third embodiment, the first negative electrode layer 34 may be composed of the first negative electrode active material and the mixed phase 37 composed of a mixture of hard carbon and a solid electrolyte.
[0162] (Fourth Embodiment)
[0163] Figure 4It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to a fourth embodiment of the present invention.
[0164] like Figure 4 As shown, the negative electrode layer 41 of the sodium ion secondary battery 40 is composed of a second negative electrode active material 47 as a matrix and a particulate first negative electrode active material 46 arranged in the matrix.
[0165] The first negative electrode active material 46 includes a carbon material. As the first negative electrode active material 46, the materials described in the first negative electrode active material 6 of the first embodiment can be used as appropriate.
[0166] The second negative electrode active material 47 includes a sodium-containing alloy. As the sodium-containing alloy, the sodium-containing alloy described in the second negative electrode active material of the first embodiment can be used as appropriate.
[0167] The content of the first negative electrode active material 46 in the negative electrode layer 41 is not particularly limited, but is preferably 45% by mass or more, more preferably 70% by mass or more, and preferably 97% by mass or less, more preferably 85% by mass or less. In this case, the battery characteristics such as the charge and discharge capacity of the sodium ion secondary battery 40 can be further improved.
[0168] The content of the second negative electrode active material 47 in the negative electrode layer 41 is not particularly limited, but is preferably 3% by mass or more, more preferably 15% by mass or more, preferably 55% by mass or less, and more preferably 30% by mass or less. In this case, the initial charge and discharge efficiency and cycle characteristics of the sodium ion secondary battery 40 can be further improved.
[0169] The negative electrode layer 41 can be formed, for example, by the following method.
[0170] First, the negative electrode layer 41 can be formed by applying a slurry for forming the negative electrode layer 41 onto the second main surface 2 b of the solid electrolyte layer 2 , drying the slurry, and firing the slurry.
[0171] Examples of the slurry for forming the negative electrode layer 41 include a slurry containing a first negative electrode active material 46 such as hard carbon, a second negative electrode active material 47 such as a sodium-containing alloy, and, if necessary, a binder and a conductive additive.
[0172] As in the fourth embodiment, the negative electrode layer 41 may be a single-layer negative electrode layer composed of the second negative electrode active material 47 as a matrix and the particulate first negative electrode active material 46 arranged in the matrix.
[0173] (Fifth Embodiment)
[0174] Figure 5 It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to a fifth embodiment of the present invention.
[0175] like Figure 5 As shown, the negative electrode layer 51 of the sodium ion secondary battery 50 includes a particulate first negative electrode active material 56 , a particulate second negative electrode active material 57 , and a solid electrolyte 52 a .
[0176] The first negative electrode active material 56 includes a carbon material. As the first negative electrode active material 56, the material described in the first negative electrode active material 6 of the first embodiment can be used.
[0177] The second negative electrode active material 57 includes a sodium-containing alloy. As the sodium-containing alloy, the sodium-containing alloy described in the second negative electrode active material included in the second negative electrode layer 5 of the first embodiment can be used.
[0178] The solid electrolyte 52a is not particularly limited, and water glass (Na2O-nSiO2·xH2O) (n=0.5 to 4), sodium silicate (Na2O-nSiO2) (n=0.5 to 4), etc. can be used. Among them, water glass can also be used as a binder when forming the negative electrode layer 51, so it can be used appropriately.
[0179] The content of the first negative electrode active material 56 in the negative electrode layer 51 is not particularly limited, but is preferably 20% by mass or more, more preferably 45% by mass or more, and preferably 92% by mass or less, more preferably 77% by mass or less. In this case, the battery characteristics such as the charge and discharge capacity of the sodium ion secondary battery 50 can be further improved.
[0180] The content of the second negative electrode active material 57 in the negative electrode layer 51 is not particularly limited, but is preferably 1% by mass or more, more preferably 3% by mass or more, and preferably 52% by mass or less, more preferably 27% by mass or less. In this case, the initial charge and discharge efficiency and cycle characteristics of the sodium ion secondary battery 50 can be further improved.
[0181] The content of the solid electrolyte 52a in the negative electrode layer 51 is not particularly limited, but is preferably 5% by mass or more, more preferably 10% by mass or more, and preferably 50% by mass or less, more preferably 30% by mass or less. In this case, the ion conductivity in the negative electrode layer 51 can be further improved.
[0182] The negative electrode layer 51 can be formed, for example, by the following method.
[0183] First, for example, the negative electrode layer 51 can be formed by applying a slurry for forming the negative electrode layer 51 onto the second main surface 2 b of the solid electrolyte layer 2 , and performing press bonding after drying and firing.
[0184] Examples of the slurry for forming the negative electrode layer 51 include a slurry containing a first negative electrode active material 56 such as hard carbon, a second negative electrode active material 57 such as a sodium-containing alloy, a precursor of the solid electrolyte 52 a , and, if necessary, a binder, a solvent, and a conductive additive.
[0185] In the second to fifth embodiments as well, the negative electrode layer contains not only the first negative electrode active material containing the carbon material but also the second negative electrode active material containing the sodium alloy, thereby improving the initial charge and discharge efficiency of the sodium ion secondary battery and improving the cycle characteristics.
[0186] In the first to fifth embodiments, the sodium ion secondary battery is described as an all-solid-state sodium ion secondary battery. However, the sodium ion secondary battery may be an electrolyte-based sodium ion secondary battery as in the sixth to ninth embodiments.
[0187] [Sixth to Ninth Embodiments]
[0188] (Sixth Embodiment)
[0189] Figure 6 It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to a sixth embodiment of the present invention.
[0190] like Figure 6 As shown, the sodium ion secondary battery 60 is an electrolyte-based sodium ion secondary battery including a positive electrode layer 3 , a negative electrode layer 61 (negative electrode for sodium ion secondary battery), an electrolyte 62 , a separator 68 , and a current collector 69 .
[0191] The negative electrode layer 61 includes a first negative electrode layer 64 and a second negative electrode layer 65. The second negative electrode layer 65 is provided on the current collector 69. The first negative electrode layer 64 is provided on the second negative electrode layer 65. Thus, the first negative electrode layer 64 is provided on the positive electrode layer 3 side.
[0192] The first negative electrode layer 64 contains a first negative electrode active material 6. The first negative electrode active material 6 contains a carbon material. As the first negative electrode active material 6, the materials described in the first embodiment can be used as appropriate.
[0193] The content of the first negative electrode active material 6 in the first negative electrode layer 64 is not particularly limited, but is preferably 70% by mass or more, more preferably 90% by mass or more, preferably 97% by mass or less, and more preferably 95% by mass or less. In this case, the battery characteristics such as the charge and discharge capacity of the sodium ion secondary battery 60 can be further improved.
[0194] The second negative electrode layer 65 contains a second negative electrode active material. The second negative electrode active material contains a sodium-containing alloy. In addition, as the second negative electrode layer 65, the negative electrode layer described in the second negative electrode layer 5 of the first embodiment can be used. The positive electrode layer 3 and the current collector 69 can also appropriately use the materials described in the first embodiment.
[0195] As the electrolyte 62, for example, an organic solvent electrolyte, an ionic liquid, etc. can be used. As the organic solvent electrolyte, for example, 1M NaPF6 EC:DEC, 1M NaPF6PC, etc. can be used. In addition, as the ionic liquid, for example, NaFSI, NaTFSI, Pyr13FSI, EMIMFSI, MPPyFSI, etc. can be used.
[0196] The negative electrode layer 61 can be formed, for example, by the following method.
[0197] First, the second negative electrode layer 65 is formed on the current collector 69 such as aluminum foil. The second negative electrode layer 65 can be formed by forming a film containing a sodium alloy by, for example, sputtering or vapor deposition.
[0198] Next, the slurry for forming the first negative electrode layer 64 is applied onto the second negative electrode layer 65 , and after drying and firing, it is pressed and bonded to form the first negative electrode layer 64 , thereby forming the negative electrode layer 61 .
[0199] Examples of the slurry for forming the first negative electrode layer 64 include a slurry containing the first negative electrode active material 6 such as hard carbon and, if necessary, a binder, a solvent, and a conductive additive.
[0200] (Seventh Embodiment)
[0201] Figure 7 It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to a seventh embodiment of the present invention.
[0202] like Figure 7 As shown, in the negative electrode layer 71 of the sodium ion secondary battery 70, the first negative electrode layer 64 and the second negative electrode layer 65 are sequentially provided on the collector 69. Thus, in the negative electrode layer 71, the second negative electrode layer 65 is provided on the positive electrode layer 3 side. Figure 7 In the sixth embodiment, the second negative electrode layer 65 is described as being in a linear shape, but in reality, the second negative electrode layer 65 is provided so as to cover the material of the first negative electrode layer 64. Other aspects are the same as those of the sixth embodiment.
[0203] As in the seventh embodiment, in the electrolyte-based sodium ion secondary battery 70 , the second negative electrode layer 65 may be disposed on the positive electrode layer 3 side.
[0204] (Eighth Embodiment)
[0205] Figure 8 It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to an eighth embodiment of the present invention.
[0206] like Figure 8 As shown, the negative electrode layer 81 of the sodium ion secondary battery 80 includes a particulate first negative electrode active material 86 and a particulate second negative electrode active material 87 .
[0207] The first negative electrode active material 86 includes a carbon material. As the first negative electrode active material 86, the materials described in the first negative electrode active material 6 of the first embodiment can be used as appropriate.
[0208] The second negative electrode active material 87 includes a sodium-containing alloy. As the sodium-containing alloy, the sodium-containing alloy described in the second negative electrode active material of the first embodiment can be used as appropriate.
[0209] The content of the first negative electrode active material 86 in the negative electrode layer 81 is not particularly limited, but is preferably 45% by mass or more, more preferably 70% by mass or more, and preferably 97% by mass or less, more preferably 85% by mass or less. In this case, the battery characteristics such as the charge and discharge capacity of the sodium ion secondary battery 80 can be further improved.
[0210] The content of the second negative electrode active material 87 in the negative electrode layer 81 is not particularly limited, but is preferably 3% by mass or more, more preferably 15% by mass or more, preferably 55% by mass or less, and more preferably 30% by mass or less. In this case, the initial charge and discharge efficiency and cycle characteristics of the sodium ion secondary battery 80 can be further improved.
[0211] The negative electrode layer 81 can be formed, for example, by the following method.
[0212] First, for example, a slurry for forming the negative electrode layer 81 is applied onto the current collector 69 such as aluminum foil, and after drying and firing, the slurry is pressed and bonded, thereby forming the negative electrode layer 81 .
[0213] As the slurry for forming the negative electrode layer 81, for example, there can be cited a slurry containing a first negative electrode active material 86 such as hard carbon, a second negative electrode active material 87 such as a sodium alloy, and a binder, a solvent, and a conductive additive as required. In addition, as the binder, the binder described in the first embodiment can be used, and water glass (Na2O-nSiO2) can also be used. In the case where the binder is water glass, the adhesiveness can be further improved.
[0214] As in the eighth embodiment, the negative electrode layer 81 may be a single negative electrode layer including the particulate first negative electrode active material 86 and the particulate second negative electrode active material 87 .
[0215] (Ninth Embodiment)
[0216] Fig. 9 It is a schematic cross-sectional view showing a negative electrode for a sodium ion secondary battery and a sodium ion secondary battery according to a ninth embodiment of the present invention.
[0217] like Fig. 9 As shown, the negative electrode layer 91 of the sodium ion secondary battery 90 is composed of a second negative electrode active material 97 as a matrix and a particulate first negative electrode active material 96 arranged in the matrix.
[0218] The first negative electrode active material 96 includes a carbon material. As the first negative electrode active material 96, the materials described in the first negative electrode active material 6 of the first embodiment can be used as appropriate.
[0219] The second negative electrode active material 97 includes a sodium-containing alloy. As the sodium-containing alloy, the sodium-containing alloy described in the second negative electrode active material of the first embodiment can be used as appropriate.
[0220] The content of the first negative electrode active material 96 in the negative electrode layer 91 is not particularly limited, but is preferably 45% by mass or more, more preferably 70% by mass or more, and preferably 97% by mass or less, more preferably 85% by mass or less. In this case, the battery characteristics such as the charge and discharge capacity of the sodium ion secondary battery 90 can be further improved.
[0221] The content of the second negative electrode active material 97 in the negative electrode layer 91 is not particularly limited, but is preferably 3% by mass or more, more preferably 15% by mass or more, preferably 55% by mass or less, and more preferably 30% by mass or less. In this case, the initial charge and discharge efficiency and cycle characteristics of the sodium ion secondary battery 90 can be further improved.
[0222] The negative electrode layer 91 can be formed, for example, by the following method.
[0223] First, for example, a slurry for forming the negative electrode layer 91 is applied onto the current collector 69 such as aluminum foil, and after drying and firing, the slurry is pressed and bonded, thereby forming the negative electrode layer 91 .
[0224] Examples of the slurry for forming the negative electrode layer 91 include a slurry containing a first negative electrode active material 96 such as hard carbon, a second negative electrode active material 97 such as a sodium-containing alloy, and, if necessary, a binder and a conductive aid.
[0225] As in the ninth embodiment, the negative electrode layer 91 may be a single-layer negative electrode layer composed of the second negative electrode active material 97 as a matrix and the particulate first negative electrode active material 96 arranged in the matrix.
[0226] As in the sixth to ninth embodiments, in the sodium ion secondary battery of the electrolyte system, the negative electrode layer contains not only a first negative electrode active material comprising a carbon material, but also a second negative electrode active material comprising a sodium alloy, thereby being able to improve the initial charge and discharge efficiency of the sodium ion secondary battery and to improve the cycle characteristics.
[0227] Hereinafter, the present invention will be described in more detail based on specific examples, but the present invention is not limited to the following examples and can be implemented with appropriate changes within the scope of the present invention.
[0228] (Example 1)
[0229] (a) Preparation of solid electrolyte layer
[0230] A solid electrolyte layer composed of β″-alumina having a thickness of 50 μm was prepared.
[0231] (b) Preparation of slurry for forming the first negative electrode layer
[0232] To obtain a composition of Na3Zr2Si2PO 12 The sodium superion conductor (NASICON) type crystal was prepared by weighing a total of 25 g of sodium silicate: Na2O·3SiO2, ammonium zirconium carbonate aqueous solution ((NH4)2Zr(OH)2(CO3)2), sodium tripolyphosphate (Na5P3O 10 ). Add 150g of pure water thereto and stir at 50°C for 24 hours. Thus, a sodium ion conductive solid electrolyte precursor solution (pH = 9.7) is obtained. Next, the solution is allowed to stand overnight in a thermostatic bath at 5°C to gel. Thus, a sodium ion conductive solid electrolyte precursor is prepared. Next, dry it in a dryer at 60°C for 12 hours, and then vacuum dry it at 100°C for 6 hours to obtain a powder of a sodium ion conductive solid electrolyte precursor. Next, crush the above powder into a powdery state using an agate mortar.
[0233] The powder of the sodium ion conductive solid electrolyte precursor and the conductive aid (acetylene black) are weighed and mixed in a weight ratio of 19:1 to obtain a mixed powder. With respect to 30 parts by mass of the mixed powder, 70 parts by mass of hard carbon powder (average particle size D50: 1 μm) are mixed to obtain a negative electrode composite material powder. Furthermore, with respect to 100 parts by mass of the negative electrode composite material powder, 15 parts by mass of polypropylene carbonate (PPC) as a binder is added, and N-methyl-2-pyrrolidone as a solvent is added in such a manner that the concentration of the negative electrode composite material powder is 50 parts by mass. The mixture is mixed with a rotation-revolution mixer to prepare a slurry for forming the first negative electrode layer.
[0234] (c) Preparation of positive electrode slurry
[0235] The glass powder (BET specific surface area: 35 m 2 / g), β″-alumina as a solid electrolyte and acetylene black (AB) as a conductive aid were mixed in a mass ratio of 83:12:5 to obtain a positive electrode composite material powder. With respect to 100% by mass of the positive electrode composite material powder, 12% by mass of polypropylene carbonate was added as a binder, and N-methyl-2-pyrrolidone as a solvent was added in a manner such that the solid content concentration of the positive electrode composite material and the binder was 50% by mass. The mixture was mixed with a rotation and revolution mixer to prepare a slurry for positive electrode formation.
[0236] (d) Preparation of the first negative electrode layer
[0237] The slurry for forming the first negative electrode layer is applied in the center of one main surface of a solid electrolyte layer of 12 mm square and 50 μm thick in a manner of 50 μm thickness and 10 mm square, and dried in a thermostatic chamber at 60°C for 1 hour. Then, it is fired at 800°C for 2 hours in an N2 (99.99%) atmosphere to form the first negative electrode layer. The load weight of the first negative electrode layer is calculated as (the weight of the stack after the first negative electrode layer is formed) - (the weight of the solid electrolyte layer). The calculated load weight is multiplied by the ratio of the first negative electrode active material, i.e., hard carbon, 0.8, and the calculated load amount of the first negative electrode active material in the first negative electrode layer is 3.5 mg / cm 2 In addition, the capacity of the first negative electrode layer was calculated by assuming that the capacity of the hard carbon was 300 mAh / g. As a result, the capacity of the first negative electrode layer was 1.05 mAh / cm 2 .
[0238] (e) Preparation of positive electrode layer
[0239] The positive electrode slurry is applied in the center of the main surface of the solid electrolyte layer on the side opposite to the first negative electrode layer in a thickness of 400μm and 10mm square. After drying in a constant temperature bath at 60°C for 2 hours, it is fired in an N2 / H2 (96 / 4 by volume ratio) atmosphere at 500°C for 30 minutes to form a positive electrode layer. The load weight of the positive electrode layer is calculated based on (the weight of the stack after the positive electrode layer is formed) - (the weight of the stack before the positive electrode is formed). The calculated load weight is multiplied by the proportion of the positive electrode active material therein 0.83 to calculate the weight of Na2FeP2O7 as the positive electrode active material. The load amount of the positive electrode active material in the positive electrode layer is 10.5mg / cm 2 Assuming that the capacity of Na2FeP2O7 crystallized glass (Na2FeP2O7 as the positive electrode active material) per gram is 97 mAh / g, the capacity of the positive electrode layer is calculated. The result is that the capacity of the positive electrode layer is 1.02 mAh / cm2 .
[0240] (f) Formation of the current collector and the second negative electrode layer and assembly of button cells
[0241] On the entire surface of the positive electrode layer, an aluminum vapor-deposited film with a thickness of 500 nm is formed as a current collector. Then, in an argon glove box, a sodium-containing alloy Na9Sn4 is formed on the first negative electrode layer as a second negative electrode active material by vacuum evaporation to form a second negative electrode layer, thereby forming a negative electrode layer (negative electrode for sodium ion secondary battery). The loading amount of the second negative electrode active material in the second negative electrode layer is 0.46 mg / cm 2 , thickness is 1.8μm.
[0242] The obtained electric storage element was sealed in a CR2032 button battery to prepare a test battery (sodium ion secondary battery).
[0243] (g) Charge and discharge test
[0244] In a constant temperature chamber at 30°C, a constant current charge and discharge test of the test battery was performed. Specifically, based on the capacity of the positive electrode layer, the current value of 0.05C rate (20 hours of charge and discharge) was used, the charge capacity, discharge capacity and operating voltage were measured by charging at a cut-off voltage of 4.5V and discharging at a cut-off voltage of 1.5V. In addition, the ratio of the first discharge capacity to the first charge capacity was calculated as the first charge and discharge efficiency.
[0245] (Examples 2 to 8)
[0246] In the second negative electrode layer, the type of sodium-containing alloy, the amount of the second negative electrode active material loaded in the second negative electrode layer, and the thickness of the second negative electrode layer were changed as shown in Table 1 below. A test cell (sodium ion secondary battery) was prepared in the same manner as in Example 1, and a charge and discharge test was performed. The results are shown in Table 1 below.
[0247] [Table 1]
[0248]
[0249] (Example 9)
[0250] A test battery (sodium ion secondary battery) was prepared in the same manner as in Example 1, and a charge and discharge test was performed, except that (b) a slurry for forming a first negative electrode layer, (d) a first negative electrode layer, and (f) a current collector and a second negative electrode layer were formed and assembled into a button battery as described below.
[0251] (b) Preparation of slurry for forming the first negative electrode layer
[0252] To obtain a composition of Na3Zr2Si2PO 12The sodium superion conductor (NASICON) type crystal was prepared by weighing a total of 25 g of sodium silicate: Na2O·3SiO2, ammonium zirconium carbonate aqueous solution ((NH4)2Zr(OH)2(CO3)2), sodium tripolyphosphate (Na5P3O 10 ). 150 g of pure water was added thereto, and the mixture was stirred at 50°C for 24 hours. Thus, a sodium ion conductive solid electrolyte precursor solution (pH = 9.7) was obtained. Next, the solution was allowed to stand overnight in a thermostatic bath at 5°C to gel. Thus, a sodium ion conductive solid electrolyte precursor was prepared.
[0253] Sucrose (sucrose), which is a hard carbon source of a carbon electrode material precursor, and the sodium ion conductive solid electrolyte precursor were mixed in a stirrer at a weight ratio of 7:1 for 1 hour to obtain a mixture. Then, the mixture was dried in a dryer at 60°C for 12 hours, and then vacuum dried at 100°C for 6 hours to obtain a powder of a mixture of the sodium ion conductive solid electrolyte precursor and the carbon electrode material precursor. Then, the powder of the mixture was crushed into a powdery state using an agate mortar.
[0254] The powder of the mixture of the obtained sodium ion conductive solid electrolyte precursor and the carbon electrode material precursor is weighed and mixed with a conductive aid (acetylene black) in a weight ratio of 19:1 to obtain a mixed powder. 40 parts by mass of hard carbon powder (average particle size D50: 1 μm) is mixed with 60 parts by mass of the mixed powder to obtain a negative electrode composite material powder. Furthermore, 15% by mass of polypropylene carbonate (PPC) as a binder is added to 100% by mass of the negative electrode composite material powder, and N-methyl-2-pyrrolidone as a solvent is added so that the concentration of the negative electrode composite material powder is 50% by mass. This is mixed with a rotation and revolution mixer to prepare a slurry for forming the first negative electrode layer.
[0255] (d) Preparation of the first negative electrode layer
[0256] The slurry for forming the first negative electrode layer is applied in the center of one main surface of a solid electrolyte layer of 12 mm square and 50 μm thick in a manner of 50 μm thickness and 10 mm square, and dried in a thermostatic chamber at 60°C for 1 hour. Then, it is fired at 800°C for 2 hours in an N2 (99.99%) atmosphere to form the first negative electrode layer. The load weight of the first negative electrode layer is calculated as (the weight of the stack after the first negative electrode layer is formed) - (the weight of the solid electrolyte layer). The calculated load weight is multiplied by the ratio of the first negative electrode active material, i.e., hard carbon (the amount of hard carbon derived from sucrose and the mixed hard carbon) 84wt%, and the calculated load amount of the first negative electrode active material in the first negative electrode layer is 3.5mg / cm 2In addition, the capacity of the first negative electrode layer was calculated by assuming that the capacity of the hard carbon mixture was 300 mAh / g. As a result, the capacity of the first negative electrode layer was 1.04 mAh / cm 2 .
[0257] (f) Formation of the current collector and the second negative electrode layer and assembly of button cells
[0258] On the entire surface of the positive electrode layer, an aluminum vapor-deposited film with a thickness of 500 nm is formed as a current collector. Then, in an argon glove box, a sodium-containing alloy Na9Sn4 is formed on the first negative electrode layer as a second negative electrode active material by vacuum evaporation to form a second negative electrode layer, thereby forming a negative electrode layer (negative electrode for sodium ion secondary battery). The loading amount of the second negative electrode active material in the second negative electrode layer is 0.28 mg / cm 2 , thickness is 1.1μm.
[0259] The obtained electric storage element was sealed in a CR2032 button battery to prepare a test battery (sodium ion secondary battery).
[0260] (Example 10 to Example 16)
[0261] In the second negative electrode layer, the type of sodium-containing alloy, the loading amount of the second negative electrode active material in the second negative electrode layer, and the thickness of the second negative electrode layer are changed as shown in Table 2 below. Otherwise, a test battery (sodium ion secondary battery) is prepared in the same manner as in Example 9 and a charge and discharge test is carried out.
[0262] The results are shown in Table 2 below.
[0263] [Table 2]
[0264]
[0265] (Example 17)
[0266] A test battery (sodium ion secondary battery) was prepared in the same manner as in Example 1, and a charge and discharge test was performed, except that (b) a slurry for forming a first negative electrode layer, (d) a first negative electrode layer, and (f) a current collector and a second negative electrode layer were formed and assembled into a button battery as described below.
[0267] (b) Preparation of slurry for forming the first negative electrode layer
[0268] To obtain a composition of Na3Zr2Si2PO 12 The sodium superion conductor (NASICON) type crystal was prepared by weighing a total of 25 g of sodium silicate: Na2O·3SiO2, ammonium zirconium carbonate aqueous solution ((NH4)2Zr(OH)2(CO3)2), sodium tripolyphosphate (Na5P3O 10). 150 g of pure water was added thereto, and the mixture was stirred at 50°C for 24 hours. Thus, a sodium ion conductive solid electrolyte precursor solution (pH = 9.7) was obtained. Next, the solution was allowed to stand overnight in a thermostatic bath at 5°C to gel. Thus, a sodium ion conductive solid electrolyte precursor was prepared.
[0269] Sucrose (sucrose), which is a hard carbon source of a carbon electrode material precursor, and the sodium ion conductive solid electrolyte precursor were mixed in a stirrer at a weight ratio of 7:1 for 1 hour to obtain a mixture. Then, the mixture was dried in a dryer at 60°C for 12 hours, and then vacuum dried at 100°C for 6 hours to obtain a powder of a mixture of the sodium ion conductive solid electrolyte precursor and the carbon electrode material precursor. Then, the powder of the mixture was crushed into a powdery state using an agate mortar.
[0270] The obtained mixture of the sodium ion conductive solid electrolyte precursor and the carbon electrode material precursor powder and the conductive auxiliary agent (acetylene black) were weighed and mixed in a weight ratio of 19:1 to obtain a negative electrode composite material. With respect to 100% by mass of the negative electrode composite material powder, 15% by mass of polypropylene carbonate (PPC) as a binder was added, and N-methyl-2-pyrrolidone as a solvent was added in a manner that the concentration of the negative electrode composite material powder was 50% by mass. The mixture was mixed with a rotation and revolution mixer to prepare a slurry for forming the first negative electrode layer.
[0271] (d) Preparation of the first negative electrode layer
[0272] The slurry for forming the first negative electrode layer is applied in the center of one main surface of a solid electrolyte layer of 12 mm square and 50 μm thick in a manner of 50 μm thickness and 10 mm square, and dried in a thermostatic chamber at 60°C for 1 hour. Then, it is fired at 800°C for 2 hours in an N2 (99.99%) atmosphere to form the first negative electrode layer. The load weight of the first negative electrode layer is calculated as (the weight of the stack after the first negative electrode layer is formed) - (the weight of the solid electrolyte layer). The calculated load weight is multiplied by the proportion of the first negative electrode active material, i.e., hard carbon derived from sucrose, which is 75wt%, and the calculated load amount of the first negative electrode active material in the first negative electrode layer is 2.6 mg / cm 2 In addition, the capacity of the first negative electrode layer was calculated by assuming that the capacity of the hard carbon derived from sucrose was 400 mAh / g. As a result, the capacity of the first negative electrode layer was 1.04 mAh / cm 2 .
[0273] (f) Formation of the current collector and the second negative electrode layer and assembly of button cells
[0274] On the entire surface of the positive electrode layer, an aluminum vapor-deposited film with a thickness of 500 nm is formed as a current collector. Then, in an argon glove box, a sodium-containing alloy Na9Sn4 is formed on the first negative electrode layer as a second negative electrode active material by vacuum evaporation to form a second negative electrode layer, thereby forming a negative electrode layer (negative electrode for sodium ion secondary battery). The loading amount of the second negative electrode active material in the second negative electrode layer is 0.46 mg / cm 2 , thickness is 1.8μm.
[0275] The obtained electric storage element was sealed in a CR2032 button battery to prepare a test battery (sodium ion secondary battery).
[0276] (Example 18)
[0277] In the second negative electrode layer, the type of sodium-containing alloy, the loading amount of the second negative electrode active material in the second negative electrode layer, and the thickness of the second negative electrode layer are changed as shown in Table 3 below. Otherwise, a test battery (sodium ion secondary battery) is prepared in the same manner as in Example 17, and a charge and discharge test is carried out.
[0278] The results are shown in Table 3 below.
[0279] [Table 3]
[0280]
[0281] (Comparative Example 1)
[0282] A test cell (sodium ion secondary battery) was prepared in the same manner as in Example 1 except that the following metal layer was formed in place of the second negative electrode layer, and a charge and discharge test was performed.
[0283] Preparation of metal layer:
[0284] In an argon glove box, a metal Al film was formed on the first negative electrode layer by vacuum evaporation to form a metal layer. The loading amount of the metal layer was 0.1 mg / cm 2 , thickness is 0.4μm.
[0285] (Comparative Example 2)
[0286] A test cell (sodium ion secondary battery) was prepared in the same manner as in Example 9 except that the following metal layer was formed in place of the second negative electrode layer, and a charge and discharge test was performed.
[0287] Preparation of metal layer:
[0288] In an argon glove box, a metal Al film was formed on the first negative electrode layer by vacuum evaporation to form a metal layer. The loading amount of the metal layer was 0.1 mg / cm 2 , thickness is 0.4μm.
[0289] (Comparative Example 3)
[0290] A test cell (sodium ion secondary battery) was prepared in the same manner as in Example 1 except that the following metal layer was formed in place of the second negative electrode layer, and a charge and discharge test was performed.
[0291] Preparation of metal layer:
[0292] In an argon glove box, a metal Sn film was formed on the first negative electrode layer by vacuum evaporation to form a metal layer. The loading amount of the metal layer was 0.3 mg / cm 2 , thickness is 1.2μm.
[0293] The results are shown in Table 4 below.
[0294] [Table 4]
[0295]
[0296] Description of Reference Numerals
[0297] 1, 21, 31, 41, 51, 61, 71, 81, 91… negative electrode layer
[0298] 10, 20, 30, 40, 50, 60, 70, 80, 90…Sodium ion secondary battery
[0299] 2…Solid electrolyte layer
[0300] 2a…first main surface
[0301] 2b…Second main surface
[0302] 3… Positive electrode layer
[0303] 4, 24, 34, 64…First negative electrode layer
[0304] 5, 65…Second negative electrode layer
[0305] 6, 46, 56, 86, 96…first negative electrode active material
[0306] 7. 52a…Solid electrolyte
[0307] 27, 37…Mixed phase
[0308] 47, 57, 87, 97…Second negative electrode active material
[0309] 62…Electrolyte
[0310] 68…Diaphragm
[0311] 69…current collector.
Claims
1. A negative electrode for a sodium ion secondary battery, comprising: a first negative electrode active material including a carbon material; and The second negative electrode active material includes a sodium alloy.
2. The negative electrode for a sodium ion secondary battery according to claim 1, comprising: a first negative electrode layer containing the first negative electrode active material; and The second negative electrode layer contains the second negative electrode active material.
3. The negative electrode for a sodium ion secondary battery according to claim 2, wherein: The second negative electrode layer also serves as a current collector.
4. The negative electrode for a sodium ion secondary battery according to claim 1 or 2, wherein The sodium-containing alloy is an alloy containing Na and Sn.
5. The negative electrode for a sodium ion secondary battery according to claim 4, wherein The sodium-containing alloy is Na X Sn, where 0.16≤x≤3.
75.
6. The negative electrode for a sodium ion secondary battery according to claim 2 or 3, wherein: The second negative electrode layer has a thickness of 0.3 μm or more and 10 μm or less.
7. The negative electrode for a sodium ion secondary battery according to claim 1 or 2, wherein: The carbon material is hard carbon.
8. The negative electrode for a sodium ion secondary battery according to claim 1 or 2, wherein: The negative electrode for a sodium ion secondary battery further contains a solid electrolyte.
9. The negative electrode for a sodium ion secondary battery according to claim 8, wherein The solid electrolyte contains at least one selected from the group consisting of β″-alumina, β-alumina, and sodium superion conductor crystals. 10 . A sodium ion secondary battery, comprising the negative electrode for a sodium ion secondary battery according to claim 1 or 2.
11. The sodium ion secondary battery according to claim 10, wherein: The negative electrode for the sodium ion secondary battery further includes a solid electrolyte layer, The negative electrode for the sodium ion secondary battery is provided on one main surface of the solid electrolyte layer.
12. The sodium ion secondary battery according to claim 11, wherein: The negative electrode for the sodium ion secondary battery comprises: A first negative electrode layer, which is provided on the solid electrolyte layer side and contains the first negative electrode active material; and The second negative electrode layer is provided on the main surface of the first negative electrode layer on the side opposite to the solid electrolyte layer, and contains the second negative electrode active material.
Citation Information
Patent Citations
All-solid battery
JP2010015782A